Oligonucleotide directed mutagenesis of Escherichia coli 5S ribosomal RNA: construction of mutant and structural analysis. - Göringer, H U (1984)
The ribosomal 5S RNA gene from the rrnB operon of E. coli was mutagenised in vitro using a synthetic oligonucleotide hybridised to M13 ssDNA containing that gene. The oligonucleotide corresponded to the 5S RNA sequence positions 34 to 51 and changed the guanosine at position 41 to a cytidine. The DNA containing the desired mutation was identified by dot blot hybridisation and introduced back into the plasmid pKK 3535 which contains the total rrnB operon in pBR 322. Plasmid coded 5S rRNA was selectively labeled with 32p using a modified maxi-cell system, and the replacement of guanosine G41 by cytidine was confirmed by RNA sequencing. The growth of cells containing mutant 5S rRNA was not altered by the base change, and the 5S rRNA was processed and incorporated into 50S ribosomal subunits and 70S ribosomes. The structure of wildtype and mutant 5S rRNA was compared by chemical modification of accessible guanosines with kethoxal and limited enzymatic digestion using RNase T1 and nuclease S1. These results showed that the wildtype and mutant 5S rRNA do not differ significantly in their structure. Furthermore, the formation, interconversion and stability of the two 5S rRNA A- and B-conformers are unchanged.